2003
DOI: 10.1007/s00428-003-0782-6
|View full text |Cite
|
Sign up to set email alerts
|

The reappraisal of gastrointestinal stromal tumors: from Stout to the KIT revolution

Abstract: For five decades gastrointestinal stromal tumors (GISTs) truly have represented one of the most confusing as well as neglected areas of both surgical pathology and clinical oncology. The recognition of the central role played by KIT expression in the development of the interstitial cell of Cajal and of the activating KIT mutations in the pathogenesis of GIST have been the keys for a more precise categorization of this long elusive clinicopathological entity. A Consensus Conference held at the National Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…GISTs most commonly occur in the stomach and small intestine [10, 11]. In this study, more cases were located in the stomach and small intestine in accordance with the literature (stomach localization is 43% (15/35), for small bowel it is 34% (12/35)).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…GISTs most commonly occur in the stomach and small intestine [10, 11]. In this study, more cases were located in the stomach and small intestine in accordance with the literature (stomach localization is 43% (15/35), for small bowel it is 34% (12/35)).…”
Section: Discussionsupporting
confidence: 87%
“…They appear everywhere from the esophagus to the rectum, but most commonly they occur in the stomach and small intestine [10, 11]. 60–70% occur in the stomach, 25–35% in the small intestine, 5% in the colon, rectum or appendix, and 2–3% in the esophagus [1, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Miettinen et al have demonstrated that spindle cell histology of GIST presents poor prognosis (21). Furthermore, lower cellularity has been described as a useful prognostic factor, while severe nuclear atypia has been mostly seen in aggressive tumors (23,24). In our study, cell type, cellularity, and nuclear pleomorphism had no statistically significant effect on recurrence.…”
Section: Discussionsupporting
confidence: 40%
“…Advance in pathology, immunohistochemistry and molecular biology in recent years has greatly improved the diagnosis of GIST. It is now considered that GISTs arise from interstitial Cajal cells (ICCs), expressing CD117 (product of c-kit proto-oncogene), and harboring c-kit or platelet-derived growth factor receptor alpha (PDGFRA) gain-of-function mutation [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%